Enhancement of polymer hydrophobicity by SF6 plasma treatment and argon plasma immersion ion implantation - Rangel, E. C.; Bento, W. C.A.; Kayama, M. E.; Schreiner, W. H.; Cruz, N. C. (Wiley, 2003)
In this study sulphur hexafluoride (SF6) plasmas and argon plasma immersion ion implantation (ArPIII) techniques have been applied to improve the hydrophobicity of poly(tetrafluoroethylene) (PTFE), polyurethane and silicone surfaces. As evaluated by water contact angle measurements, all the treatments resulted in a signifcant enhancement in the hydrophobicity of the polymers. However, exposure of the treated samples to air induced a strong variation in their hydrophobicity as a consequence of post-plasma reactions between atmospheric species and remnant surface free radicals. X-ray photoelectron spectroscopy results strongly suggest that for polyurethane and silicone the surface fluorination by SF6 plasmas and the creation of new carbon bonds and radicals are the main agents for hydrophobicity enhancement. The PTFE exposed to ArPIII revealed increases in the contact angles after exposure to air. A significant incorporation of oxygen and the formation of new carbon bonds were revealed by XPS measurements. Copyright © 2003 John Wiley & Sons, Ltd.
Keywords: Contact angle; PDMS; Plasma; Plasma immersion ion implantation; Polyurethane; PTFE